Change in Design Features of Tribocouplings of ICE Parts to Increase their Wear Resistance and Durability - V. A. et al., Kochenov (International Journal of Advanced Science and Technology, 2020)
Design solutions to increase durability and wear resistance of tribocouplings of the crank mechanism and cylinder and piston assembly have been developed based on the regularities of wear, load variation, and reallocation during operation. With the variety and spread of the factors that determine durability and wear resistance, change in wear and wear rate during operation has an expressed consistent character.